PENERAPAN PENDEKATAN HUMANISTIS PADA PERKULUAHAN EVALUASI PEMBELAJARAN DI PGSD BONE - Sudarto, Sudarto (JISOS: JURNAL ILMU SOSIAL, 2022)
The problems that related to student abilities have always been an interesting discussion from various groups, especially academic circles. Lots of research has been conducted in order to improve the student abilities, but most of it was still based on a purely cognitive approach. Based on theoretical studies, a learning theory that provided more opportunities for students to optimally developed their potential was humanistic learning theory. The research method used in this research was the pre-experimental method with a one shoot case study design. The data collected and processed was student ability data in the form of student acquisition scores from doing assignments and tests. The results showed that the ability of students in this course ranged from grade 3 or grade B and grade 4 or grade A. Overall, the average student ability was 3.59, far exceeding from the target to be achieved, namely an average score of 3. All students look happy, active and serious in participating in the. lectures